The Relevance of Judicial Considerations in Sentencing Perpetrators of Human Trafficking for Transnational Exploitation: A Case Study of Decision Number 567/Pid.Sus/2025/PN.Tjk - Althafi, Fahmi Dwi; Limantara, Benny Karya (The Future of Education Journal, 2026)
Human trafficking is considered an extraordinary crime due to its complex and multidimensional nature, often involving organized criminal networks. This study aims to analyze judicial considerations in sentencing perpetrators of transnational exploitation in Decision Number: 567/Pid.Sus/2025/PN.Tjk and examine their relevance in terms of legal certainty, justice, and utility. The research uses normative and empirical juridical approaches, utilizing both secondary and primary data collected through library and field research, analyzed qualitatively. The findings indicate that judicial considerations are based on the fulfillment of all legal elements under Law Number 21 of 2007. Judges also consider the defendant’s role in the network, level of culpability, and impact on victims. These considerations reflect sentencing objectives and principles of criminal responsibility. In terms of legal certainty, the decision provides clear application of legal norms. From the perspective of justice, it balances the offender’s fault and the victim’s suffering. In terms of utility, the ruling is expected to create a deterrent effect and support prevention, although victim protection and recovery still require strengthening. It is recommended that judges consistently apply legal provisions comprehensively while prioritizing victim protection. Policymakers should enhance victim recovery mechanisms through restitution, rehabilitation, continuous assistance, and improved inter-agency coordination.